Кристаллизация полимера из расплавленного состояния и из его растворов в условиях наложенного механического поля - Шамбилова, Г.К. (Изд-во КарГУ, 2010)
Концентрацияланған ерітіндіден алынған полидодеканамидтің кристалданған индукциялық периодына ығысу жылдамдығының əсері зерттелген. Сонда ығысу деформациясының кристалдану жылдамдығына едəуір əсері бар екені көрсетілген жəне ығысу деформациясының төменгі жылдамдықтар аймағында кристалдану ұлғая түседі, ал жоғарғы аймақтарда индукциялық кезең қалыптасады. The influence of shear rate on the induction period of crystallization of poly(dodecanamide) from its melt and concentrated solutions have been studied. It was proven that shearing strongly influences the kinetics of crystallization. Meanwhile, there are two domains of shear rate. At low shear rates, shearing promtes the process of crystallization, while crystallization slows down at very high shear rates. These results have been explained basing on the conception of the influence of shear stresses on the intensity of nucleation and a possibility of the destroying primary nuclei under the action of high stresses.
Polymer crystallization from melt and solutions under superimposed shear field
Keywords: полимер; кристаллизация; физика полимеров; структурообразование; кинетика; индукционный период; скорость; температура; концентрация в растворе